1998
DOI: 10.1021/jf970709y
|View full text |Cite
|
Sign up to set email alerts
|

Retention of Aroma Compounds by Carbohydrates: Influence of Their Physicochemical Characteristics and of Their Physical State. A Review

Abstract: Many aroma compounds, used to flavor food products, are used in a solid state, after encapsulation. Carbohydrates are the most common matrices used to entrap these volatiles. It has been observed that depending on the aroma compound and the carrier, efficiency can vary. This article reviews the influence of physicochemical properties of both the volatiles and the carriers on retention. The latter depends on the functional groups of the aroma compound. Moreover, it increases with molecular weight and decreases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
140
1
13

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(160 citation statements)
references
References 60 publications
6
140
1
13
Order By: Relevance
“…The retention of lenthionine increased markedly as DE was decreased. Goubet et al, 13) reported a similar result in the effect of DE on the flavor retention. Voilley and Simatos 14) explained that the greater retention observed with a high molecular weight carrier is due to the reduction of duffusivity of flavor during drying.…”
Section: Resultsmentioning
confidence: 59%
“…The retention of lenthionine increased markedly as DE was decreased. Goubet et al, 13) reported a similar result in the effect of DE on the flavor retention. Voilley and Simatos 14) explained that the greater retention observed with a high molecular weight carrier is due to the reduction of duffusivity of flavor during drying.…”
Section: Resultsmentioning
confidence: 59%
“…The type of matrix material used can strongly influence the tablet properties (Stroh et al 2000) and the oxidation stability of the encapsulated compounds (Schrooyen et al 2000). The stability against oxidation is related to the O 2 -permeability of the matrix (Baisier & Reineccius, 1989;Goubet et al 1998). The diffusion of gases such as O 2 through the capsule wall depends on the state of the polymer mixture composing the capsule.…”
Section: Vitaminsmentioning
confidence: 99%
“…They are produced by acid or enzymatic hydrolysis of starches, or even a combination of both processes (Chronakis, 1998). The use of maltodextrin offers several advantages, such as low cost, high solubility, low viscosity and excellent protection of flavors against oxidation(CanoChauca et al, 2005; Goubet et al, 1998;Reineccius, 1991). Also, maltodextrins with high molarmass and low value of dextrose equivalent (DE) provide high physical stability to the wall matrix system (Bae and Lee, 2008).The modified starch is an encapsulating agent commonly used for their encapsulation abilities, such as excellent retention of volatiles (above 93%), the stabilization of the emulsion and low viscosity (Arancibia et al, 2011).…”
Section: Introductionmentioning
confidence: 99%